Microstructural studies of improved meat chopped semi-finished products - Paska, Maria; Masliichuk, Olga (Technology audit and production reserves, 2017)
In many countries of the world, including in Ukraine, there is insufficient provision of the population with protein foods. So, the deficit of protein in the diet of the population of Ukraine is at least 25 %. Dishes made from chopped meat cutlets for energy value is necessary for human nutrition. However, at present, close attention is paid to the principles of healthy nutrition based on a balanced food composition, the presence in it of all the substances and elements necessary for maintaining the health and vitality of the body. Therefore, it is proposed to introduce into the meat cut semi-finished products the powder of the elecampane root and the white lupine flour. Essential oil of a complex composition (lactones, alantol and proazulen) contains in the rhizomes and roots of elecampane. In addition to essential oil, inulin is found (up to 44 %), inulinen, pseudoinulin, acetic and benzoic acids. And also elecampane stimulates the reproduction of the population of the necessary bifidobacteria in the large intestine. Lupine flour is rich in proteins and dietary fiber. Improved ground beef with replace 5 %, 10 %, 15 % of the meat portion of lupine flour and the addition of 0.5 % of elecampane root powder and a control sample of ground beef are considered. For microscopic examination, the material of the minced meat is labeled and fixed in a 10 % neutral formalin solution. On the sledge microtome, sections 0.5–1 cm thick are made dyed with hematoxylin and eosin – periodic acid Schiff reaction. Histological studies have shown for the periodic acid Schiff reaction the content of meat and vegetable parts in the developed semi-finished product. By hematoxylin and eosin, the percentage composition of the minced meat is determined. So, thanks to the development of functional meat chopped products, it is possible to achieve health-rational nutrition. The introduction of the elecampane root helps restore the strength and health of people, and lupine flour allows the product to be enriched with proteins.